Some novel ways of gastric cancer patients treatment personification - Kirkilevsky, S. I.; Lurín, A. G.; Dubinina, V. G.; Lukyanchuk, O. V.; Mashukov, A. A.; Bilenko, A. A.; Zgura, A. N.; Osadchy, D. N.; Maksimovskiy, V. E. (Journal of Education, Health and Sport, 2017)
In this paper the authors perform the analysis of molecular and morphological factors influencing the survival of patients with gastric cancer (n = 221). They analyzed the survival rate in this group of patients based on the analysis of molecular markers VEGFR, p53, Her2, Ki-67. Measured role in the survival such factors as the degree of differentiation of primary gastric tumors, the presence of microscopic tumor involvement of perineural and perivascular spaces, the degree of invasion to gastric wall by T1 = 1 and to T4a = 4, T4b = 5, number of regional lymph nodes affected by metastasis, and other factors. As an arbitrator used survival curves calculated by the method of R. J. Cox, time of lifespan, measured in months, as well as a comparison of the areas under the curves of survival.